In vitro evaluation of phosphorothioate oligonucleotides targeted to the E2 mRNA of papillomavirus: potential treatment for genital warts. - Cowsert, L M (1993)
Papillomaviruses induce benign proliferative lesions, such as genital warts, in humans. The E2 gene product is thought to play a major role in the regulation of viral transcription and DNA replication and may represent a rational target for an antisense oligonucleotide drug action. Phosphorothioate oligonucleotides complementary to E2 mRNAs were synthesized and tested in a series of in vitro bovine papillomavirus (BPV) and human papillomavirus (HPV) models for the ability to inhibit E2 transactivation and virus-induced focus formation. The most active BPV-specific compounds were complementary to the mRNA cap region (ISIS 1751), the translation initiation region for the full-length E2 transactivator (ISIS 1753), and the translation initiation region for the E2 transrepressor mRNA (ISIS 1755). ISIS 1751 and ISIS 1753 were found to reduce E2-dependent transactivation and viral focus formation in a sequence-specific and concentration-dependent manner. ISIS 1755 increased E2 transactivation in a dose-dependent manner but had no effect on focus formation. Oligonucleotides with a chain length of 20 residues had optimal activity in the E2 transactivation assay. On the basis of the above observations, ISIS 2105, a 20-residue phosphorothioate oligonucleotide targeted to the translation initiation of both HPV type 6 (HPV-6) and HPV-11 E2 mRNA, was designed and shown to inhibit E2-dependent transactivation by HPV-11 E2 expressed from a surrogate promoter. These observations support the rationale of E2 as a target for antiviral therapy against papillomavirus infections and specifically identify ISIS 2105 as a candidate antisense oligonucleotide for the treatment of genital warts induced by HPV-6 and HPV-11.